Vaccine-induced specific cellular and humoral immunity after MRNA-based COVID-19 vaccination in athletes and controls - Klemis, V.; Schmidt, T.; Venhorst, A.; Halmans, L.; Marx, S.; Hielscher, F.; Urschel, R.; Guckelmus, C.; Greiß, F.; Sester, U.; Gärtner, B. C.; Meyer, T.; et al. (Medicine & Science in Sports & Exercise, 2025)
Purpose High-performance sports training has been associated with immunomodulatory activity on vaccine-induced immunity in athletes. To date, it is unknown whether training in athletes may affect immunogenicity of mRNA-based vaccines, as the vaccine antigen is produced in the muscle.